Thyroid testing in pregnant women with thyroid dysfunction in Tayside, Scotland: the thyroid epidemiology, audit and research study (TEARS). (25th January 2013) - Vadiveloo, Thenmalar; Mires, Gary J.; Donnan, Peter T.; Leese, Graham P.
Summary Objective To investigate the rate of thyroid testing during pregnancy. Design Population‐based, retrospective record‐linkage study. Setting Health care data on pregnant women in Tayside, Scotland. Participants All pregnant women who were 18 years and above and who delivered between 1 January 1993 and 31 March 2011 in Tayside were identified. Patients were included in the study if they have had at least three thyroxine prescriptions prior to pregnancy of which at least one prescription was within 6 months prior to pregnancy. Main outcome measures Number of thyroid‐stimulating hormone (TSH) assays performed during pregnancy and the changes in dosage of thyroxine prescribed during pregnancy. Results We identified 950 pregnancies that had thyroxine prescribed prior to pregnancy. Overall, 96·9% (95% CI: 96–98) of these pregnancies had at least one TSH assay performed during or just prior to pregnancy, with 81·2% (95% CI: 79–84) in the first trimester. The prescription of thyroxine was increased in 60·0% (95% CI: 57–63) at any time during pregnancy and in 34·0% (95% CI: 31–37) of pregnancies during the first trimester. Overall, 60% (95% CI: 57–63) of pregnancies had at least one elevated serum TSH during pregnancy with 55% (95% CI: 51–58) in the first trimester. Conclusion The TSH concentration is raised in many pregnancies in women taking long‐term thyroxine.